Change in nutritional status among women of childbearing age in India (1998-2016) - Sanni Yaya; Bishwajit Ghose (Wiley, 2020)
Summary Introduction In absolute numbers, India has more undernourished people than all the countries in sub‐Saharan Africa combined. In parallel with the high rates of hunger and undernutrition, the country has been undergoing rapid demographic and dietary transition marked by an increased prevalence of overweight/obesity, particularly among women. Objective To measure the changing prevalence of overnutrition during last two decades, as well as to identify the associated sociodemographic correlates among pregnant and non‐pregnant women in India. Methods This was a cross‐sectional study based on data from the latest round of National Family Health Survey (2015-2016) conducted among urban and rural women. Participants were 687,876 women (655,850 non‐pregnant and 32,026 pregnant) aged between 15 and 49 years. Nutritional status was assessed in terms of body mass index (BMI) using the cut‐off for Asian population. Results Since 1998-1999, the prevalence of underweight has decreased by 9.2%, while that of overweight (BMI = 23-27.4 kg/m2) and obesity (BMI ≥ 27.5 kg/m2) has increased by 6.7% and 3.4%, respectively. Results of multivariable regression analysis revealed significant association between nutritional status and age, parity residency, educational level, religious affiliation, household wealth quintile, and TV watching behaviour. Of those, age and wealth status appeared to be the strongest predictors among both pregnant and non‐pregnant women. Conclusion Since 1998, there has been a considerable drop in the prevalence of underweight and rise in the prevalence of overweight and obesity. Significant sociodemographic variations exist in nutritional status, notably age and financial situation, which should be highlighted in national nutrition policymaking and intervention programmes.